The organizational climate and teaching performance at the Universidad "Jaime Bausate y Meza" Jesús María - Lima, 2016 - Barriga Rodríguez, Rhomao Diego (2022)
The organizational climate that has the following dimensions: human talent, organizational design and organizational culture for two structured data collection and measurement variables and consists of two questionnaires were prepared. The teacher performance variable covers the following dimensions: teaching skills, responsibility performance, interpersonal relationships and results of the educational work that was applied to 40 teachers in the sample. We find that the correlation coefficient Spearman Rho is GOOD p_ 0.755 and 0.001 value is therefore we see that there is a direct relationship and a significance level of less than 0.05 why is rejected the null hypothesis and the alternative hypothesis that suggests that organizational climate is related to teacher performance at the University "Bausate and Jaime Meza" is accepted. Jesus Maria. 2016 Lima construct validity.